KIMIA DARAH KUDA LOKAL LUAR NEGERI YANG DIPELIHARA DI DAERAH ISTIMEWA YOGYAKARTA (DIY) DAN JAWA TENGAH - , JUERA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The horse population maintained in Indonesian is decreasing by years. This case describes that the horse are at risk of extinction. One of the factors causing these extinctions is the presence of the disease in horses. Therefore need to know the identification or normal blood chemistry to describe horse organs bred in DIY and Central Java. The purpose of this research to determine normal standards, covering Serum Glutamic Transaminase (SGPT) Piruvic, Serum Glutamic Oxaloacetic Transaminase (SGOT), Blood Urea Nitrogen (BUN) and Creatinin on a foreign horse which was kept in Yogyakarta ( DIY ) and Central Java.This research result was expected to be one of the reference clinic chemical Medic Veteriner and beneficial in disease, eradication effort especially diseases of the kidneys and liver of a horse. Seven foreign horses sample from Bantul (DIY), Salatiga, and Semarang (Central Java) has taken blood samples to be tested SGPT, SGOT, BUN and Creatinin. Seven samples of foreign horses are clinically healthy and do not show pathological, reproduction defect or disorder. Blood sample taking using disposable syrink 10 ml without an anticoagulant stored 5 ml through the jugular vein.Then disposable syring be tilted so as to obtain serum.The serum horse analyzed by using automatic blood analyzer model RT-1940C (Synchron clinical system CX5CE, Beckam USA) Chemical parameters blood data has served as average, range and standard deviations.The result showed that range value Serum Glutamic Piruvic Transaminase (SGPT) by 6,38 - 16,18 IU /L, Serum Glutamic Oxaloacetic Transaminase (SGOT) by 225,86 - 334,14 IU /L, Blood Urea Nitrogen (BUN) by 9,39 â 18,65 mg/dL, and Creatinin by 0,82 â 1,82 mg/dL. This research has an equivalence with literature.